Quality of Life, Urogynecological Morbidity, and Lymphedema After Radical Vaginal Trachelectomy for Early-Stage Cervical Cancer. Issue 4 (1st May 2015) - Frøding, Ligita Paskeviciute; Ottosen, Christian; Mosgaard, Berit Jul; Jensen, Pernille Tine
Abstract : Objective: Radical vaginal trachelectomy (RVT) offers a possibility for future childbearing for young women with early-stage cervical cancer. However, the literature on quality of life and self-reported morbidity in patients undergoing RVT is scarce. The aim of this study was to prospectively assess quality of life after RVT with focus on urogynecological morbidity and lymphedema. Furthermore, the aim of this study was to compare results with those in women treated with radical abdominal hysterectomy (RAH) and with age-matched control women from the general population. Methods and Materials: Eighteen patients with early-stage cervical cancer operated with RVT were prospectively included and assessed preoperatively, 3, 6, and 12 months postoperatively using validated questionnaires. Thirty-two patients treated with RAH were included consecutively and assessed once at 12 months postsurgery, whereas an age-matched control group of 30 healthy women was assessed once. Results: Fifty percent of the RVT group and 41% of the RAH reported any grade of incomplete bladder emptying problems at 1 year postsurgery assessment. Eleven percent of the RVT patients and 12.5% of the RAH patients reported severe lymphedema of the legs as assessed by the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Cervical Cancer Module. The Global Health Status scores of the RVT patients improved over time but were significantly lower than in the healthy controls during the entire observation time ( P = 0.029). Conclusions: Patients treated with RVT for early-stage cervical cancer had persistent bladder emptying problems and lymphedema comparable to those experienced by patients treated with RAH and significantly higher than those reported by healthy control women.